Twelfth Five Year Plan 2012-2017 and Annual Plan 2012-2013 Draft Proposals Government of Meghalaya - Planning Commission (Planning Commission, 2012)
Meghalaya emerged as a full-fledged State of the Indian Union on 21st January, 1972. It is strategically located in the North-East between 25° 5” and 26° 10” North Latitudes and between 98° 47” and 97° 47” East Longitudes, bounded by Bangladesh on the South as well as partly on the West (international boundary about 443 Km) and surrounded on the other sides by Assam. The State’s area of 22,429 sq.km is spread across the predominantly three hill regions of Garo Hills, Jaintia Hills and Khasi Hills. Administratively, the State is divided into 7 Districts, 8 Civil Sub-divisions and 39 C&RD Blocks.
Government of Meghalaya, Planning Department